Hippuristanol Reduces the Viability of Primary Effusion Lymphoma Cells both in Vitro and in Vivo - Masachika Senba; Naoki Mori; Junichi Tanaka; Harutaka Katano; Chie Ishikawa (Marine Drugs, 2013)
Primary effusion lymphoma (PEL) caused by Kaposi’s sarcoma-associated herpesvirus (also known as human herpesvirus-8) shows serious lymphomatous effusion in body cavities. PEL is difficult to treat and there is no standard treatment strategy. Hippuristanol is extracted from Okinawan coral Isis hippuris, and inhibits translational initiation by blocking eukaryotic initiation factor 4A, an ATP-dependent RNA helicase, binding to mRNA. Recently, there has been much interest in targeting translation initiation as an anticancer therapy. Here, we show that treatment of PEL cell lines with hippuristanol resulted in cell cycle arrest at G1 phase, and induced caspases activation and apoptosis. Hippuristanol also reduced the expression of cyclin D2, CDK2, CDK4, CDK6 and prosurvival XIAP and Mcl-1 proteins. Activation of activator protein-1, signal transducers and activators of transcription protein 3 and Akt pathways plays a critical role in the survival and growth of PEL cells. Hippuristanol suppressed the activities of these three pathways by inhibiting the expression of JunB, JunD, c-Fos, signal transducers and activators of transcription protein 3 and Akt proteins. In a xenograft mouse model that showed ascites and diffused organ invasion of PEL cells, treatment with hippuristanol significantly inhibited the growth and invasion of PEL cells compared with untreated mice. The results of the in vitro and in vivo experiments underline the potential usefulness of hippuristanol in the treatment of PEL.